2017
DOI: 10.1007/s00464-017-5556-3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic liver re-resection is feasible for patients with posthepatectomy hepatocellular carcinoma recurrence: a propensity score matching study

Abstract: Laparoscopic liver re-resection for patients with posthepatectomy HCC recurrence provided comparable perioperative and oncological outcomes as open liver re-resection and can be a safe alternative to open procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 42 publications
2
64
0
Order By: Relevance
“…No significant differences in terms of baseline patient characteristics, including tumor size were reported by the total of the studies. Furthermore, they all demonstrated a significantly lower blood loss rate in favor of RLLR, which resulted in decreased blood transfusion requirements and improved operative outcomes (Table II) (27,28,30). Operative time was significantly lower in one study (19) in favor of the laparoscopic approach with the rest of the studies demonstrating non-significant differences.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…No significant differences in terms of baseline patient characteristics, including tumor size were reported by the total of the studies. Furthermore, they all demonstrated a significantly lower blood loss rate in favor of RLLR, which resulted in decreased blood transfusion requirements and improved operative outcomes (Table II) (27,28,30). Operative time was significantly lower in one study (19) in favor of the laparoscopic approach with the rest of the studies demonstrating non-significant differences.…”
Section: Resultsmentioning
confidence: 94%
“…Operative time was significantly lower in one study (19) in favor of the laparoscopic approach with the rest of the studies demonstrating non-significant differences. Length of stay was significantly shorter, in 4 out of 5 studies, in the RLLR group (26)(27)(28)30). Postoperative morbidity was evaluated in 4 studies (26-28, 30) with 3 of them presenting a significantly decreased morbidity rate in the RLLR group when compared to ROLR.…”
Section: Resultsmentioning
confidence: 99%
“…However, the overall 5-year survival rate remains unsatisfactory. 2 Major challenges in treating HCC are the limitations of surgical management for patients with advanced HCC, high recurrence after surgery and the lack of efficient drugs with mild side effects. Sorafenib is the first targeted therapeutic agent available for advanced HCC and exerts antitumor effects by inhibiting tumor cell proliferation, preventing angiogenesis and inducing cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the minimally invasive of the abdominal wall could cause less bleeding in the LRLR and LPLR groups. [8,9,11,12,24,25] With respect to the intraoperative conversion, although Liu et al, [17] van der Poel et al [21] and Noda et al [19] reported some patients with the severe intra-abdominal adhesions were converted to open surgery, the pooled data suggested that the conversion rate was comparable between the LRLR and LPLR groups. These results indicated LRLR was safe during procedures, but it is noticeable that these LRLRs enrolled in this study were mainly performed by experienced surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…There are some limitations in our studies. First, although most of the included trials were conducted with case-matched, [13,14,16,17,2022] in the absence of RCTs examining LRLR versus ORLR for recurrent tumors, selection bias regarding the selection of surgical approach was unavoidable. Second, some of the studies were not provided the important basic statistics, such as the surgical approach of previous hepatectomy and the grade of adhesions.…”
Section: Discussionmentioning
confidence: 99%